Synthesis and characterization of new azobenzene-containing bis pentacyanoferrate(II) stoppered push–pull [2]rotaxanes, with α- and β-cyclodextrin. Towards highly medium responsive dyes. (February 2015) - Deligkiozi, Ioanna; Voyiatzis, Evangelos; Tsolomitis, Athanase; Papadakis, Raffaello
Abstract: The solvatochromic behavior of novel synthesized azo-containing viologen-based rotaxanes, combining push–pull linear and α or β-cyclodextrin macrocyclic components is examined. These rotaxanes are stoppered by pentacyanoferrate(II) units. The latter stabilize these systems and furthermore act as strong electron donors. These units are linked to strong electron withdrawing viologen units thus giving rise to an exceptionally intense solvatochromic behavior. Suitable solvent polarity scales and Linear Solvation Energy Relationships (LSERs) were employed in order to rationalize the solvent polarity effects observed, both specific and non-specific ones. The results for the title compounds as well as their Cyclodextrin-Free-Dumbbell (CFD) like analogue, are compared to recent published solvatochromic data regarding similar smaller pentacyanoferrate(II) complexes as well as other highly solvatochromic compounds. Structural effects on the solvatochromic intensity as well as the contribution of different solvent-solute interactions are rationalized and quantified. Graphical abstract: Highlights: Pentacyanoferrate complexes with azobenzene based ligands were synthesized. Corresponding chromotropic [2]rotaxanes were synthesized and characterized. The prominent solvatochromism of these push–pull dyes was investigated. Binary solvent mixtures were used for the study of solvatochromism. Medium and structural effects were quantified and rationalized.